The effect of binder mycotoxins on the histopathology of broiler kidneys exposed to a combination of mycotoxins - Anastasya, Jelita; Mirni Lamid; Poedji Hastutiek; Erma Safitri; Mohammad Anam Al-Arif; Hani Plumeriastuti (Jurnal Agro Veteriner, 2025)
This study was made to know the histopathological changes of kidney in broiler chicken fed by mix mycotoxin (aflatoxin B1 and ochratoxin A) contaminated feed. A total of 20 chickens aged DOC to 35 days was divided into 4 groups (K-, K+, P1 and P2) each group consisted of 5 chickens. Group K- as a control without the addition of the mix mycotoxin to the fed. Group K+ feed was added with 0.1 mg/kg of aflatoxin B1 and 0.1 mg/kg of ochratoxin A. Group P1 and P2 feed were added mix mycotoxin with the same dose with addition of 1.1 g/kg mycotoxin binder in P1 group and 1.6 g/kg of mycotoxin binder in P2 group. Treatment of contaminated feed has been given for 28 days from day 8 until day 35. At the end of the treatment period (day 35), chickens were euthanized, and histopathological examination was carried out. Kruskal-Wallis test showed a significant difference (p<0.05) on the mean rank of the kidney cell necrosis, cell degeneration, inflammatory cell infiltration, and haemorrhage. The conclusion of this study is that the administration of mycotoxin binder has an effect in preventing and reducing the necrosis, degeneration, inflammatory cell infiltration, and kidney haemorrhage.